2014
DOI: 10.1590/0004-282x20140148
|View full text |Cite
|
Sign up to set email alerts
|

Amitriptyline and aerobic exercise or amitriptyline alone in the treatment of chronic migraine: a randomized comparative study

Abstract: To compare the preventive treatment benefits of amitriptyline and aerobic exercise or amitriptyline alone in patients with chronic migraine. Method: Sixty patients, both genders, aged between 18 and 50 years, with a diagnosis of chronic migraine, were randomized in groups called amitriptyline and aerobic exercise or amitriptyline alone. The following parameters were evaluated: headache frequency, intensity and duration of headache, days of the analgesic medication use, body mass index (BMI), Beck Depression In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 24 publications
2
70
0
3
Order By: Relevance
“…Additionally, exercise has been shown to be either additive (amitriptyline) or non‐inferior (topiramate) to pharmaceuticals in the management of migraine . 129,130 Regular exercise and physical fitness may also positively improve an athlete's mood, stress level, and sleep.…”
Section: Return To Learn and Return To Play (Rtl/rtp) Post‐mtbimentioning
confidence: 99%
“…Additionally, exercise has been shown to be either additive (amitriptyline) or non‐inferior (topiramate) to pharmaceuticals in the management of migraine . 129,130 Regular exercise and physical fitness may also positively improve an athlete's mood, stress level, and sleep.…”
Section: Return To Learn and Return To Play (Rtl/rtp) Post‐mtbimentioning
confidence: 99%
“…Supra-threshold pressure pain increased well-being, which is a known effect of physical activity (Garber et al, 2011). Previous randomized controlled trials investigating the long-term effect of aerobic exercise have found a decrease in migraine pain intensity (Dittrich et al, 2008;Varkey et al, 2011;Santiago et al, 2014). However, none of these studies have investigated the effect on pain mechanisms which make comparison of results difficult.…”
Section: Pressure Pain Thresholdsmentioning
confidence: 99%
“…Physical activity has positive effects on health and well-being (Garber et al, 2011) and has recently been found to reduce migraine burden (Krøll et al, 2018). It has shown positive effects on migraine frequency, pain intensity, pain duration (Koseoglu et al, 2003;Dittrich et al, 2008;Darabaneanu et al, 2011;Varkey et al, 2011;Overath et al, 2014;Santiago et al, 2014) and quality of life (Narin et al, 2003;Dittrich et al, 2008;Varkey et al, 2009). However, the mode of action of physical activity in migraine with regards to pain mechanisms is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…One RCT comparing isolated amitriptyline versus amitriptyline associated with aerobic exercise three times a week in the management of chronic migraine showed a greater reduction in the frequency of headache days in the combined approach group 122 .…”
Section: Physical Activitymentioning
confidence: 99%